VLDL receptor gene therapy for reducing atherogenic lipoproteins - Ronald M. Krauss; Jonathan T. Lu; Joseph J. Higgins; Cathryn M. Clary; Ray Tabibiazar (Elsevier, 2023)
Over the past 40 years, there has been considerable research into the management and treatment of atherogenic lipid disorders. Although the majority of treatments and management strategies for cardiovascular disease (CVD) center around targeting low-density lipoprotein cholesterol (LDL-C), there is mounting evidence for the residual CVD risk attributed to high triglyceride (TG) and lipoprotein(a) (Lp(a)) levels despite the presence of lowered LDL-C levels. Among the biological mechanisms for clearing TG-rich lipoproteins, the VLDL receptor (VLDLR) plays a key role in the trafficking and metabolism of lipoprotein particles in multiple tissues, but it is not ordinarily expressed in the liver. Since VLDLR is capable of binding and internalizing apoE-containing TG-rich lipoproteins as well as Lp(a), hepatic VLDLR expression has the potential for promoting clearance of these atherogenic particles from the circulation and managing the residual CVD risk not addressed by current lipid lowering therapies. This review provides an overview of VLDLR function and the potential for developing a genetic medicine based on liver-targeted VLDLR gene expression.